Exposure to low concentrations of PM2.5 and its constituents with preterm birth in Shenzhen, China: a retrospective cohort study - Minting Zhu; Zhongai Ouyang; Tao Liu; Weigui Ni; Zhijian Chen; Bingyi Lin; Lijuan Lai; Yi Jing; Long Jiang; Jingjie Fan (BMC Public Health)
Abstract Background Due to the Air Pollution Prevention and Control Measures issued by the Chinese government, air quality has significantly improved, particularly with respect to PM2.5. However, studies on the relationship between low concentrations of PM2.5 and preterm birth (PTB) remain limited in China. Objective To examine the associations between low concentrations of PM2.5 and its constituents and PTB. Methods This retrospective cohort study was conducted from July 2021 to April 2023 in Shenzhen, China. Data on questionnaires and pregnancy outcomes were collected for each participant. Using the Tracking Air Pollution in China (TAP) dataset, we assessed the concentrations of PM2.5 and its chemical constituents, including sulfate (SO4 2−), nitrate (NO3 −), organic matter (OM), black carbon (BC), and ammonium (NH4 +). We applied a generalized additive model (GAM) to evaluate the relationship. The relationship between exposure to PM2.5 and its constituents and PTB was further examined using a method that combined dummy variable settings with trend tests. Stratified analysis was conducted to explore the potential factors. Results Among 17,240 live-born infants, the rate of PTB was 6.0%, and the average exposure concentration of PM2.5 was 20.24 μg/m3. There were positive associations between PM2.5 and its constituents and PTB. With each interquartile range (IQR) increase in PM2.5 during the third trimester, the risk of PTB increased by 2.23 times. The exposure effects of sulfate (SO4 2−) and organic matter (OM) were comparable to the total PM2.5. The third trimester might be the critical susceptibility window. The risk was higher among women who conceived in the cold season and were exposed to higher temperatures during pregnancy. Conclusion Even at low levels, PM2.5 can still increase the risk of PTB, with varying health effects attributed to different constituents. This underscores the importance of further strengthening environmental management and characterizing the contributions of PM2.5 sources.